2003
DOI: 10.1523/jneurosci.23-03-01049.2003
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Plasticity of Peripheral Auditory Frequency Sensitivity

Abstract: Female midshipman fish (Porichthys notatus) use the auditory sense to detect and locate vocalizing males during the breeding season. Detection of conspecific vocal signals is essential to their reproductive success and can evoke strong phonotactic responses in gravid females but not in spent females that have released all of their eggs. Here, we test the hypothesis that seasonal variation in reproductive state affects the neurophysiological response properties of the peripheral auditory system in female midshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
153
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 140 publications
(167 citation statements)
references
References 53 publications
11
153
2
1
Order By: Relevance
“…This SPL level was chosen for calibration because 130 dB SPL is well above the noise floor for our measurement devices, and it is consistent with sound levels for type I male midshipman calls within and near their nests in the field and therefore within the range of stimulus amplitudes tested here (Bass and Clark 2003). The frequency stimuli used in this study were based on that used in previous studies (Sisneros and Bass 2003;Sisneros 2007Sisneros , 2009bRohmann and Bass 2011). The intentional of this study was to compare the saccular sensitivity of type II male P. notatus across season (non-reproductive vs. reproductive state) and compare the saccular sensitivity with that of females (Sisneros 2009b) and type I males (Rohmann and Bass 2011) under similar experimental conditions.…”
Section: Acoustic Stimulus Generation and Calibrationmentioning
confidence: 97%
See 2 more Smart Citations
“…This SPL level was chosen for calibration because 130 dB SPL is well above the noise floor for our measurement devices, and it is consistent with sound levels for type I male midshipman calls within and near their nests in the field and therefore within the range of stimulus amplitudes tested here (Bass and Clark 2003). The frequency stimuli used in this study were based on that used in previous studies (Sisneros and Bass 2003;Sisneros 2007Sisneros , 2009bRohmann and Bass 2011). The intentional of this study was to compare the saccular sensitivity of type II male P. notatus across season (non-reproductive vs. reproductive state) and compare the saccular sensitivity with that of females (Sisneros 2009b) and type I males (Rohmann and Bass 2011) under similar experimental conditions.…”
Section: Acoustic Stimulus Generation and Calibrationmentioning
confidence: 97%
“…This increase in type II A. A. Bhandiwad and E. A. Whitchurch contributed equally. Previous studies have shown that both the female and type I male auditory systems are seasonally adapted to detect the broadband agonistic calls and the dominant harmonic components of the advertisement calls produced by type I males during the breeding season (Sisneros and Bass 2003;Rohmann and Bass 2011). These adaptations are potentially important for conspecific detection and localization, mate choice decisions and intraspecific male competition (Sisneros 2009a, b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have investigated peripheral auditory plasticity in a teleost fish, the plainfin midshipman (Porichthys notatus Girard 1854; family Batrachoididae), that shows seasonal, reproductive state-dependent plasticity in the ability to encode the upper harmonics of vocalizations (Fig.1A,B). As females shift from a non-reproductive to a reproductive state, they exhibit a steroid-dependent improvement in frequency encoding by eighth nerve afferents to the saccule (Sisneros and Bass, 2003;Sisneros et al, 2004a), the main auditory division of the inner ear in midshipman and most teleosts (Fig.1C insert) (McKibben and Bass, 1999;Popper and Fay, 1993). We tested the hypothesis that this plasticity is not sex dependent, with males also exhibiting concurrent shifts in plasma steroid levels and auditory encoding as reflected in frequency sensitivity of the hair cell epithelium of the saccule.…”
Section: Introductionmentioning
confidence: 99%
“…The study reported here is one of a series of midshipman fish studies investigating yearly events as animals transitional between non-reproductive and reproductive states (Sisneros, 2009;Sisneros and Bass, 2003;Sisneros et al, 2004a). So far, this work has focused on females because early behavioral studies showed females exhibiting robust and consistent positive phonotaxis to playbacks mimicking male advertisement 'hums' (Fig.1A) that females use to localize nesting males (Brantley and Bass, 1994;McKibben and Bass, 1998;McKibben and Bass, 2001).…”
Section: Introductionmentioning
confidence: 99%